Course in E-learning and Moodle for Academic Staff – Development, Provision, Evaluation, Satisfaction - Angelina Kirkova-Bogdanova (UIKTEN, 2021)
The COVID-19 pandemic created challenges for education systems. Many university lecturers did not have enough training to teach in an electronic environment, for others there was no such experience at all. This paper discusses the evaluation of a course “E-learning. Moodle." designed to prepare faculty to teach online and users' satisfaction with the training. The influence of demographic and professional factors was analysed. Results indicate that confidence in computer skills and pedagogical qualification are strong predictors of the success of such training. Micro-learning with short video clips is most suitable.